Analisis Faktor Penyebab Rendahnya Minat Baca Siswa Sekolah Dasar Era Digital - Serli Almi; Mariamah; Anggih Tri Cahyadi; Mulyadi (Mataram University, 2026)
This study aims to analyze the factors influencing the low reading interest among fourth-grade elementary school students in the digital era and to describe the efforts made by teachers to improve students’ reading interest at SDN Kala. This research employed a qualitative approach with a descriptive research design. The data sources consisted of five teachers and eighteen fourth-grade students. Data were collected through observation, interviews, and documentation. Data analysis was conducted through the stages of data reduction, data interpretation, and conclusion drawing. Data validity was ensured through theory triangulation and source triangulation. The findings revealed that the low reading interest of students was influenced by both internal and external factors. Internal factors included low reading motivation, a lack of reading habits, and difficulties in comprehending reading materials. External factors included excessive use of gadgets and digital media, limited family support for reading culture, inadequate school literacy facilities, and the use of less innovative teaching methods. Furthermore, the study found that teachers had implemented various strategies to enhance students’ reading interest, such as establishing reading routines before lessons, providing classroom reading corners, utilizing engaging learning media, integrating educational digital media, and collaborating with parents to foster a reading culture at home. These findings indicate that improving elementary school students’ reading interest in the digital era requires collaboration among schools, teachers, families, and the wider community through strengthening literacy culture and promoting the educational use of digital technology.